EVT730: Environmental Spatial Modelling / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2021)
This course aims to provide students with knowledge to simulate spatially and temporally variable environmental impacts via spatial environmental modeling. Simulation provides to ask the answer ‘what if’ questions that can be used to guide decision-making strategies of complex environmental problem that do not respect political or physical boundaries: eg., forest fire, deforestation, flood prone, nonpoint source (NPS) pollution. It also covers various data mining technique and soft computing approaches for environmental modeling using GIS technique. Data mining principles in GIS, processing, modeling, interpretation, mapping will also discussed. Furthermore, the course will also discuss on the uncertainty that can also result from data error. In this course the student will have hands-on practical of using specific software to simulate a model on selected environmental application.